Vaporwave, or music optimised for abandoned malls - Glitsos, Laura (Cambridge University Press, 2018)
In this article I focus on the genre of ‘vaporwave’, using the artist 18 Carat Affair as a case study, to explore the way the genre works as a project that produces, and takes pleasure in, a kind of ‘memory play’. As a genre, vaporwave is a style of music collaged together from a wide variety of largely background musics such as muzak®, 1980s elevator music and new age ambience. Vaporwave's ‘memory play’ is a project that takes remembering as its audio-visual aesthetic. The pleasure of vaporwave is therefore understood as a pleasure of remembering for the sake of the act of remembering itself. To explore this theme, I examine vaporwave's memory play using the terms of Chris Healy's ‘compensatory nostalgia’, as well as the idea of ‘ersatz nostalgia’ as discussed by Arjun Appadurai and Svetlana Boym.